2014
DOI: 10.1007/s10989-014-9397-9
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of N α -Protected Amino/Peptide Hydroxamic Acids Mediated by COMU

Abstract: One-pot preparation of N a -protected amino/ peptide hydroxamic acids from corresponding carboxylic acids is described using uronium-type coupling reagent COMU. The present protocol is simple and mild conditions are used. Thus the resulting hydroxamic acids are obtained in good yields without racemization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Finally, we hydrolyzed the esters with sodium hydroxide in aqueous dioxane to give the corresponding carboxylic acids 5a–q . The hydroxamic acids 1a and 7b–q were obtained using (1-cyano-2-ethoxy-2-oxoethylidenaminooxy)­dimethylamino-morpholino-carbenium hexafluorophosphate (COMU) as an activating agent and either hydroxylamine base ( 7e–q ) or O -(tetrahydro-2 H -pyran-2-yl)­hydroxylamine ( 1a , 7b–d ), followed by acidic cleavage of the tetrahydropyranyl (THP) protecting group. On the basis of our experience, COMU was the most suitable coupling reagent because only water soluble co-products arise from this reagent which are conveniently removed during aqueous work up .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we hydrolyzed the esters with sodium hydroxide in aqueous dioxane to give the corresponding carboxylic acids 5a–q . The hydroxamic acids 1a and 7b–q were obtained using (1-cyano-2-ethoxy-2-oxoethylidenaminooxy)­dimethylamino-morpholino-carbenium hexafluorophosphate (COMU) as an activating agent and either hydroxylamine base ( 7e–q ) or O -(tetrahydro-2 H -pyran-2-yl)­hydroxylamine ( 1a , 7b–d ), followed by acidic cleavage of the tetrahydropyranyl (THP) protecting group. On the basis of our experience, COMU was the most suitable coupling reagent because only water soluble co-products arise from this reagent which are conveniently removed during aqueous work up .…”
Section: Resultsmentioning
confidence: 99%
“…In 2014, Panguluri et al 42 reported a simple, one-pot protocol under mild conditions for the synthesis of N  -protected amino/peptide hydroxamic acids from the corresponding carboxylic acids. In this protocol, COMU was used as an acid activator in the presence of a base such as DIEA to afford the target products in good yields and without any racemization.…”
Section: Special Topic Synthesismentioning
confidence: 99%
“…Furthermore, our group developed the Oxyma-B-based novel uronium-type coupling reagents TOMBU (42) and COMBU (43) (Figure 7) for use in peptide bond formation. 95 These reagents showed higher hydrolytic stability in the solvent DMF than COMU.…”
Section: Figure 7 Structures Of Oxyma-b-based Reagentsmentioning
confidence: 99%
“…11 Hydroxamic acids have been prepared by coupling mixed anhydride, obtained by the addition of carboxylic acid and ethyl chloroformate, with hydroxylamine. 7,12 Other coupling reagents like cyanuric chloride, 13 N, N'-carbonyldiimidazole (CDI), 14 1-[(1-(cyano-2ethoxy-2-oxoethylidenaminooxy)-dimethylamino-morpholinomethylene)] methaneaminium hexafluorophosphate (COMU), 15 propanephosphonic acid anhydride (T3P), 16,17 and ethyl-2-cyano-2-(4nitrophenylsulfonyloxyimino)acetate (NBsOXY), 18 were also employed to obtain hydroxamic acids from their corresponding carboxylic acids.…”
Section: Introductionmentioning
confidence: 99%